2018
DOI: 10.3747/pdi.2017.00134
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis in Orthotopic Liver Transplantation Recipients

Abstract: There appears to be no specific concern related to liver transplant patients undergoing PD. Peritonitis and mortality rates were no different from other solid organ recipients or even from the general PD population. The hepatic graft was never threatened, even during peritonitis. Therefore, these patients should not be denied the option of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Two studies allowed direct comparisons of the rate of peritonitis in LT patients to that observed in cohorts of nontransplanted PD patients (see Table 3). 16,17,20 When pooling the reported experience from this systematic review, an overall peritonitis incidence rate of 1/34 patient-months was found, which represents 0.35 infections per patient-year. This rate is slightly higher than that recently reported for general PD population in Canada (0.27; 95% CI: [0.25, 0.30]) and Australia/New Zealand (0.29; 95% CI: [0.26, 0.32]) but similar to that observed in the United Kingdom (0.35; 95% CI: [0.30, 0.40]).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Two studies allowed direct comparisons of the rate of peritonitis in LT patients to that observed in cohorts of nontransplanted PD patients (see Table 3). 16,17,20 When pooling the reported experience from this systematic review, an overall peritonitis incidence rate of 1/34 patient-months was found, which represents 0.35 infections per patient-year. This rate is slightly higher than that recently reported for general PD population in Canada (0.27; 95% CI: [0.25, 0.30]) and Australia/New Zealand (0.29; 95% CI: [0.26, 0.32]) but similar to that observed in the United Kingdom (0.35; 95% CI: [0.30, 0.40]).…”
Section: Discussionmentioning
confidence: 95%
“…Careful planning of early PD catheter insertion in patients with progressive deterioration of kidney function may also reduce the risk of requiring urgent HD initiation prior to PD by permitting sufficient time for wound healing. 11,20 Only 1 case report quantitatively mentioned dialysis adequacy using Kt/v. 21 However, all other studies reported that dialysis adequacy for these patients was within standard recommendations until the end of follow-up, death, or kidney transplantation, except for one.…”
Section: Discussionmentioning
confidence: 99%
“…This may be par- ticularly true in the case of remote events, in which clinical information may be incomplete. The option of PD is often discouraged in patients with this type of background [2][3][4][5][6], although this therapy has proven to be feasible even after seemingly aggressive abdominal procedures, including limited intestinal resections, liver transplantation [9], or bariatric surgery [10]. Computed tomography may identify overt distortions of the peritoneal structure but, in general, lacks sensitivity to detect less obvious cases.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-coagulant drugs used in HD aggravate bleeding. However, anti-coagulant drugs are not involved in PD, and thus PD may not aggravate bleeding (1). Peritoneal dialysis may also slowly clear up solutes, which could explain the previous finding that the prevalence of hypotension is relatively lower in PD than in HD (26).…”
Section: Discussionmentioning
confidence: 99%
“…A s the prevalence of end-stage renal disease (ESRD) continues to increase with the burden of chronic kidney disease, the need for a cost-effective renal replacement modality has been increasing. Peritoneal dialysis (PD) as a treatment option for patients with ESRD is an attractive therapy, providing greater cost-effectiveness and less hemodynamic stress with a lower bleeding tendency than hemodialysis (HD) (1). Another advantage of PD is less travelling for dialysis maintenance, which may appeal to patients lacking adequate transportation or living long distances from dialysis facilities (2).…”
mentioning
confidence: 99%